SIMULASI STRATEGI INVESTASI BANK DAN NON-BANK DALAM MITIGASI RISIKO KEUANGAN DIGITAL - Nayla Ahlami Dalimunthe; Tiara Marsya Aulya; Tri Ayu Fadilah; Wanda Syakinah (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to analyze the characteristics of investment instruments in banking and non-banking financial institutions, simulate portfolio investment strategies, and identify financial risk mitigation efforts in the era of digitalization. The development of financial technology has increased public access to various investment instruments, but it is also accompanied by increasing financial risks that require proper management. This study employs a descriptive qualitative approach using literature review and conceptual simulation methods. The data used are secondary data obtained from official publications of financial institutions, regulatory reports, and relevant academic literature on investment and risk management. The simulation assumes an initial investment of IDR 50,000,000 allocated into three main instruments: deposits (40%), bonds (30%), and stocks (30%), and is tested under three economic conditions, namely stable conditions, rising interest rates, and declining stock markets. The results show that a diversified portfolio generates a return of 6.32% under normal conditions, increases to 6.95% during rising interest rates, and remains positive at 4.29% during stock market downturns. These findings indicate that portfolio diversification can help reduce risk exposure and maintain investment stability under various economic conditions. Therefore, diversification-based investment strategies, risk-based instrument selection, and active portfolio management can be considered relevant approaches for financial risk mitigation in the digitalization era